Olfactory memory representations are stored in the anterior olfactory nucleus - Afif J. Aqrabawi (Nature Portfolio, 2020)
Odours are powerful stimuli used by most organisms to guide behaviour. Here, the authors identify populations of neurons within the anterior olfactory nucleus (AON) which are necessary and sufficient for the behavioural expression of odour memory.